Peridynamic simulation of finite elastic deformation and rupture in polymers. (September 2020) - Roy, Pranesh; Behera, Deepak; Madenci, Erdogan
Highlights: Peridynamics for finite elastic deformation and rupture in polymers. Arruda-Boyce material model with slight compressibility. Bond-associated deformation gradient without zero energy modes. Comparison with experimental measurements and previous simulations. Abstract: This study concerns the finite elastic deformation and rupture in styrene-butadiene rubber (SBR) and Polydimethylsiloxane (PDMS) sheets under quasi-static loading conditions. The weak form of peridynamic (PD) equilibrium equation is derived based on Anand's model and Talamini-Mao-Anand (TMA) model for polymers with slight compressibility. The nonlocal deformation gradient tensor is computed in a bond-associated domain of interaction using the PD differential operator. This approach is free of oscillations and spurious zero energy modes that are commonly observed in the PD correspondence models. Also, it permits the direct imposition of natural and essential boundary conditions. The fidelity of this PD model for predicting large deformation, progressive damage and rupture is established by comparison with experimental measurements and previous simulations of SBR and PDMS sheets with defects under displacement controlled tensile loading.